Red and blue light-specific metabolic changes in soybean seedlings - Lim, You Jin; Kwon, Soon-Jae; Eom, Seok Hyun (Frontiers in Plant Science, 2023)
Red and blue artificial light sources are commonly used as photosynthetic lighting in smart farm facilities, and they can affect the metabolisms of various primary and secondary metabolites. Although the soybean plant contains major flavonoids such as isoflavone and flavonol, using light factors to produce specific flavonoids from this plant remains difficult because the mutual regulation of light-responded flavonoids is poorly understood. In this study, a comprehensive metabolic profiling of soybean seedlings in response to red and blue lights was evaluated, and the isoflavone–flavonol regulatory mechanism under different light irradiation periods was elucidated. Comprehensive profiling of metabolites, including flavonoids, phenolic acids, amino acids, organic acids, free sugars, alcohol sugars, and sugar acids, revealed that specific flavonol, isoflavone, and phenolic acid showed light-induced high accumulation. Therefore, the metabolic gene expression level and accumulation of isoflavone and flavonol were further investigated. The light irradiation period regulated kaempferol glycoside, the predominant flavonol in soybeans, with longer light irradiation resulting in higher kaempferol glycoside content, regardless of photosynthetic lights. Notably, blue light stimulated kaempferol-3-O-(2,6-dirhamnosyl)-galactoside accumulation more than red light. Meanwhile, isoflavones were controlled differently based on isoflavone types. Malonyl daidzin and malonyl genistin, the predominant isoflavones in soybeans, were significantly increased by short-term red light irradiation (12 and 36 h) with higher expressions of flavonoid biosynthetic genes, which contributed to the increased total isoflavone level. Although most isoflavones increased in response to red and blue lights, daidzein increased in response only to red light. In addition, prolonged red light irradiation downregulated the accumulation of glycitin types, suggesting that isoflavone’s structural specificity results in different light-responded accumulation. Overall, these findings suggest that the application of specific wavelength and irradiation periods of light factors enables the regulation and acquisition of specialized metabolites from soybean seedlings.